Evaluation of appliances mobile controller system using expectation-confirmation theory model - Aslina Baharum; Chew, Yun Fai; Rozita Ismail; Ismassabah Ismail; Farhana Diana Deris; Noorsidi Aizuddin Mat Noor (Institute of Advanced Engineering and Science (IAES), 2021)
Nowadays, most Malaysians have used overpower usage of house appliances. Malaysian does not have the habit of controlling the household’s electricity consumption every day. Reducing electricity consumption is better for the earth, reducing harmful greenhouse emissions and minimizing the household's overall impact. Besides, one of the safety problems that Malaysian currently face is thieves entering the house when the owner is outstation or traveling. The proposed home appliance controller application can control and calculate the power consumption of home appliances. It can also control and set automatic timing based on the light to cause thieves to realize that the house may have people since the lights were turned on. This paper aims to identify the application features of controllers for home appliances, then develop the mobile application not only for gaming or entertainment but for better, enhanced, convenience and efficiency of lifestyle and finally to evaluate the users’ acceptance towards mobile app using expectation-confirmation theory model. Results show that perceived usefulness significant with confirmation (0.61) and continuance intentions (0.69). Perceived usefulness was demonstrated to be an essential predictor of continuance intentions (0.44). With this system or app, house appliances will be communicated and under control by the house owner.